Students' academic well-being based on the perceived social support and cognitive flexibility: a model with mediating role of psychological hardiness - Azam Vaziri Nasab; Alireza Manzari Tavakoli; Zahra Zeinaddiny Meymand; Mitra Kamyabi (Shahid Beheshti University of Medical Sciences, 2022)
Background: This study aimed to design a model of students' academic well-being based on the role of perceived social support and cognitive flexibility mediated by psychological hardiness. Methods: This study was correlational-descriptive research. The statistical sample studied in the present study was 334 people selected by stratified random sampling method among students of the Islamic Azad University of Kerman in the fiscal year of 2019-2020. The research instruments were the academic Well-being Questionnaire, Psychological Hardiness Questionnaire, Cognitive Flexibility Scale, and Perceived Social Support Scale. The pathway review process was used in Amos and SPSS software version 23 for the analysis of data. Results: The results of path analysis in the final model showed that the model had a good fit with the data. Psychological hardiness had a significant mediating role in the relationship between cognitive flexibility, social support and academic wellbeing. Results from path analysis revealed that the model has an appropriate fit with the data and psychological hardiness had a vital intermediating function in the correlation concerning cognitive flexibility, social support, and academic well-being. Model fit indicators include: Normalized Chi-square (2.17), Fit-Goodness Index (0.912), Modified Fitness-Goodness Index (0.92), Normalized Fit Index (0.96), Incremental Fit Index (0.97), Tucker-Lewis Index (0.95), Fit Index Adaptive (0.96), root mean square estimation error (0.037) has been stating that the proposed model was appropriate.  Conclusion: Psychological toughness has an important mediating role between perceived social support and cognitive flexibility with academic well-being; Therefore, efforts to develop scientific protocols to improve students' academic well-being are suggested.